Obesity in Mexican Children and Adolescents: Association to Pubertal Alterations and Muscular Strength - Talavera-Hernández, Luis Felipe; Caire-Juvera, Graciela; Jiménez-Pavón, David; Méndez-Estrada, Rosa Olivia; Portillo-Abril, Gloria Elena; Ortega-Vélez, María Isabel (International Journal of Child Health and Nutrition, 2023)
Objectives: Interventional strategies aiming to prevent obesity in children do not always consider how obesity influences the process of pubertal maturation and its implications. Additionally, maturation status could play a vital role in performing specific physical capabilities. This study aims to analyze the association of obesity, pubertal timing and tempo, and muscular strength in children and adolescents from a developing country. Methods: We measured height, weight, sitting height, estimated leg length, and waist circumference (WC) and estimated the age at peak height velocity (APHV) of 125 children (58% girls, 8.9 ± 0.4 years) and 82 adolescents (45% girls, 12.8 ± 0.3 years) from public schools in Northwest Mexico. We also collected data on physical activity, handgrip strength, and socioeconomic and demographic information. Results: Waist circumference (WC) was associated with early APHV (β = 0.006, p = 0.010) but not with a faster height gain (β = -0.012, p = 0.146). Earlier APHV and higher WC were both associated with higher handgrip strength (β = 3.86, p < 0.001; β = 0.098, p = 0.005, respectively). Conclusions: Results suggest that higher WC was related to pubertal maturation patterns and results in better muscular strength performance. This data could improve the design and implementation of interventional strategies and public policies to decrease childhood obesity.